Copper-Catalyzed Electrophilic Amination of sp2 and sp3 C−H Bonds - McDonald, Stacey L. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This thesis reports the latest developments in the direct amination of various C−H bonds using an H−Zn exchange/electrophilic amination strategy. McDonald and co-workers reveal this approach to be a rapid and powerful method for accessing a variety of functionalized amines. The material outlined in this book shows how McDonald achieved C−H zincation using strong, non-nucleophilic zinc bases and subsequent electrophilic amination of the corresponding zinc carbanions with copper as a catalyst and O-benzoylhydroxylamines as the electrophilic nitrogen source. McDonald's findings are of relevance to medicinal chemistry, drug discovery and materials science. Her thesis is a source of inspiration for scientists entering the field and students beginning their PhD in a related area. .